A interacao homem-natureza na questao da valorizacao dos recursos naturais. - Guidugli, M. M B (My University, 1984)
The values attached to natural resources have changed through time because of changes in human needs as well as technological skill. Such changes become clear in the different forms of relationship which are established between man and nature. Man must discover more adequate forms of resources use, of obtaining new supply sources, and of recovering the last equilibrium.-from English summary
The interaction man-nature in the question of the valorization of natural resources